Bronchial reactivity indices are determinants of health-related quality of life in patients with stable asthma. Issue 9 (30th August 2010) - Cisneros, Carolina; García-Río, Francisco; Romera, Delia; Villasante, Carlos; Girón, Rosa; Ancochea, Julio
Abstract : Background: A very weak relationship has been reported between the health-related quality of life (HRQL) of patients with asthma and their degree of airway hyper-responsiveness (AHR), evaluated in terms of sensitivity. However, this relationship still has not been sufficiently explored for bronchial reactivity indices. Objectives: To analyse the relationship between bronchial reactivity and sensitivity with the HRQL of patients with stable asthma, identifying the functional parameters that determine HRQL. Methods: In 103 consecutive patients with stable asthma, HRQL was evaluated using the Asthma Quality of Life Questionnaire (AQLQ). Patients underwent spirometry and non-specific bronchial provocation with methacoline. Sensitivity (PD20 ) and reactivity (dose–response slope (DRS), continuous index of responsiveness (CIR) and bronchial reactivity index (BRI)) of the dose–response curve were analysed. Results: BRI presented significant differences with different degrees of asthma severity. Although patients with AHR showed poorer quality of life than patients without AHR, the AQLQ total score was not related to PD20 but rather to DRS (r=−0.784), CIR (r=−0.712) and BRI (r=−0.776). The indices of bronchial reactivity reached a negative correlation with all the domains of the AQLQ. In a multiple linear regression model, BRI, DRS, FIV1 (forced inspiratory volume in 1 s) and VCIN (inspiratory vital capacity) were identified as independent predictors of the AQLQ total score (r 2 =0.742, p<0.001). Conclusion: In patients with stable asthma, bronchial reactivity is associated with HRQL. This could justify incorporating bronchial reactivity indices in bronchial provocation analyses.